Control of gene expression by novel metabolic intermediates. Issue 153 (September 2015) - Gustafsson, Jan-Ake
Highlights: Ligands for nuclear receptors may have affinities in the micromolar range. Ligands for estrogen receptors may be found among androgens and oxysterols. Glucose may serve as a ligand for LXR. Steroid sulfates may be NR ligands. Intestinal microbial metabolites may be receptor ligands. Abstract: In view of the recent discoveries of novel nuclear receptors (NRs) whose ligands remain to be determined, metabolic intermediates may be considered as ligands for these receptors and undiscovered or overlooked intermediates may play important roles in regulating gene expression by activating or repressing the action of these nuclear receptors. This article is part of a Special Issue entitled 'Steroid Perspectives'.